Seasonal effects on the endocrine pattern of semi-captive female Asian elephants (Elephas maximus): Timing of the anovulatory luteinizing hormone surge determines the length of the estrous cycle - C. Thitaram (2018)
Better breeding strategies for captive Asian elephants in range countries are needed to increase populations; this requires a thorough understanding of their reproductive physiology and factors affecting ovarian activity. Weekly blood samples were collected for 3.9 years from 22 semi-captive female Asian elephants in Thai elephant camps to characterize LH and progestin patterns throughout the estrous cycle. The duration of the estrous cycle was 14.6 ± 0.2 weeks (mean ± S.E.M.; n = 71), with follicular and luteal phases of 6.1 ± 0.2 and 8.5 ± 0.2 weeks, respectively. Season had no significant effect on the overall length of the estrous cycle. However, follicular and luteal phase lengths varied among seasons and were negatively correlated (r = -0.658; P < 0.01). During the follicular phase, the interval between the decrease in progestin concentrations to baseline and the anovulatory LH (anLH) surge varied in duration (average 25.9 ± 2.0 days, range 7-41, n = 23), and was longer in the rainy season (33.4 ± 1.8 days, n = 10) than in both the winter (22.2 ± 4.5 days, n = 5; P < 0.05) and summer (18.9 ± 2.6 days, n = 8; P < 0.05). By contrast, the interval between the anLH and ovulatory LH (ovLH) surge was more consistent (19.0 ± 0.1 days, range 18-20, n = 14). Thus, seasonal variation in estrous cycle characteristics were mediated by endocrine events during the early follicular phase, specifically related to timing of the anLH surge. Overall reproductive hormone patterns in Thai camp elephants were not markedly different from those in western zoos. However, this study was the first to more closely examine how timing of the LH surges impacted estrous cycle length in Asian elephants. These findings, and the ability to monitor reproductive hormones in range countries (and potentially in the field), should improve breeding management of captive and semi-wild elephants. © 2008 Elsevier Inc. All rights reserved.